2015
DOI: 10.1007/s11468-015-0038-8
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Perfect Absorber for Refractive Index Sensing and SERS

Abstract: A plasmonic perfect absorber is modeled, and its absorption/reflection properties are investigated in the visible frequency regime using finite-difference time-domain numerical simulation to show how refractive index can be measured accurately using dual interrogation technique (wavelength and intensity interrogations). Very high absorption (>95 %) is observed in the spectral range below 625 nm. The reflection and absorption spectra show a crossover (at 50 %) in which red shifts depend upon the refractive inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…This dielectric loss is the result of the coupling of a part of light to the substrate (bottom metallic layer) through LSPRs. The thickness of the bottom metallic layer is larger than the penetration depth of the incident light and also possesses high losses, and thus eliminates the transmission . The cavity confines the residual of the incident light to maximize the absorption at resonant wavelengths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dielectric loss is the result of the coupling of a part of light to the substrate (bottom metallic layer) through LSPRs. The thickness of the bottom metallic layer is larger than the penetration depth of the incident light and also possesses high losses, and thus eliminates the transmission . The cavity confines the residual of the incident light to maximize the absorption at resonant wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…In literature, different groups have calculated high sensitivities in perfect absorbers. Mandal et al, reported 530 nm per refractive index unit (RIU), Yong et al 885 nm RIU −1 , and Cheng et al 1445 nm RIU −1 . Luigi et al reported 0.25 nm V −1 for narrowband optical filter .…”
Section: Introductionmentioning
confidence: 99%
“…Perfect absorbers, which absorb a specific spectral band and do not permit reflection or transmission, have recently gained considerable interest by virtue of their wide range of applications spanning photovoltaic cells 16 , photodetectors 17,18 , thermal imaging 19 , and sensors [20][21][22][23][24][25][26][27][28] . Perfect absorbers engaging various nanostructures (e.g., plasmonic and metasurface schemes) [18][19][20][21][22][23][24][25][26][27]29 and multilayered structures [1][2][3][4]28,[30][31][32][33][34][35][36][37] are being extensively studied. Although narrowband absorbers are known to be suitable for sensing and absorption filtering 2,[25][26][27] , conventional approaches have mostly focused on multiband 21,25 or broadband absorption [31][32][33]…”
Section: Narrowband and Flexible Perfect Absorber Based On A Thin-filmentioning
confidence: 99%
“…Recently, there is increasing interesting in studying the perfect absorption of electromagnetic waves for refractive-index sensing by employing metasurfaces , metallic nanostructures , and graphene nanostructures [62][63][64][65][66][67][68][69][70][71], in violet [62], visible [1][2][3][4][5][33][34][35][36][37][38][39][40][41][42][43]63,64], infrared [6][7][8][9][10][11][12][13][14][15][16][17][44][45][46][47][48][49][50][51][52]…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there is increasing interesting in studying the perfect absorption of electromagnetic waves for refractive-index sensing by employing metasurfaces [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], metallic nanostructures [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , …”
Section: Introductionmentioning
confidence: 99%